FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEBUGARAN JASMANI PADA REMAJA SISWA KELAS XI SMK NEGERI 11 SEMARANG - Devy Amelia Nurul Alamsyah; Retno Hestiningsih; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Good physical fitness is needed by students to learn, go to school and other activities that support learning. In children and adolescents physical fitness is often forgotten especially in early adolescence, even though physical fitness is very useful to support physical work capacity in order to achieve high learning achievement. This study aims to investigate factors related to physical fitness in adolescent students at SMKN 11 Semarang. This research investigates three aspects related to physical fitness of students, i.e. Physical Activity Level, Anxiety Level and Body Mass Index. The study was conducted on students of class XI in the age range 15 - 18 years. This type of research is an analytical survey with cross sectional approach. The population is a student of grade XI with a total of 525 students, then the sample was taken as many as 183 students. Primary data consists of questionnaires to determine physical activity and anxiety levels, while weight and height measurements are required to find out the Body Mass Index. In addition, physical fitness measurements were performed using the Cooper Test method. Meanwhile, secondary data in the form of information of active student of class 2015 is obtained from the administrations office’s student center. Statistical analysis is using Spearman rank test and Pearson Product Moment correlation test. From the result of bivariate test at α=0,01, resulted in a significant positive relationship between physical activity with physical fitness (p=0,000 and r= 0,314), significant negative relation between anxiety level with physical fitness (p =0,000 and r=-0,284 ), and a significant negative relationship between Body Mass Index and Physical Fitness (p=0.000 and r=-0.272). Therefore, efforts should be made to improve healthy lifestyles and reduce the anxiety level of students by increasing physical activity to achieve good physical fitness with the end result being the increase of student achievements.